MENENTUKAN CLUSTER YANG TEPAT DENGAN K-MEANS DALAM RANGKA MENGUKUR EFEKTIVITAS PELAKSANAAN ANGGARAN PADA KEMENTERIAN AGRARIA DAN TATA RUANG/BADAN PERTANAHAN - Murti Suyoto, Indah Dewi; Rachmadi, Tri; Parulian, Lundu Taufik (ISTEK WIDURI, 2022)
The effectiveness of budget implementation is one of the benchmarks for the success of a Ministry/Agency in implementing its programs, activities and expenditures in accordance with a predetermined plan. The problem faced is that the achievement in budget execution is often not optimal, one of which is caused by the determination of inappropriate K/L budget allocations resulting in the implementation of activities that are not in accordance with the plan, the realization of budget absorption is not optimal and has the potential to cause idle cash. For this reason, it is necessary to do a mapping in order to identify the main causes or constraints in budget execution using the clustering method. This study tries to find the right cluster with the K-Means algorithm clustering method. The expected results are finding the right cluster model in measuring the effectiveness of budget implementation that can be used when determining budget allocations and preventing idle cash in the budget of the Ministry of Agrarian and Spatial Planning.